Returning to Public Transit after an Epidemic - Robin Rauws; Dea van Lierop (Findings)
The present study assesses the effect of COVID-19 related measures on public transit loyalty distinguishing between captive, choice and captive-by-choice riders. Results demonstrate that, due to fear of infection, users expect to use public transit less than before the onset of COVID-19 and report expected increases in the use of (electric) bicycles, (shared) cars and scooters. In addition, car ownership, gender, travel frequency and the possibility to work from home are other significant drivers of public transit loyalty. These findings contrast with research conducted pre-COVID-19, in which user satisfaction was commonly the most important driver of loyalty.